Hepatocyte Growth Factor Mediates the Antifibrogenic Action of Ocimum bacilicum Essential Oil against CCl4-Induced Liver Fibrosis in Rats - Hanan A. Ogaly; Nadia A. Eltablawy; Adel M. El-Behairy; Hatim El-Hindi; Reham M. Abd-Elsalam (Molecules, 2015)
The current investigation aimed to evaluate the antifibrogenic potential of Ocimum basilicum essential oil (OBE) and further to explore some of its underlying mechanisms. Three groups of rats were used: group I (control), group II (CCl4 model) and group III (OBE-treated) received CCl4 and OBE 2 weeks after the start of CCl4 administration. Oxidative damage was assessed by the measurement of MDA, NO, SOD, CAT, GSH and total antioxidant capacity (TAC). Liver fibrosis was assessed histopathologically by Masson’s trichrome staining and α-smooth muscle actin (α-SMA) immunostaining. Expression of hepatocyte growth factor (HGF) and cytochrome P450 (CYP2EI isoform) was estimated using real-time PCR and immunohistochemistry. OBE successfully attenuated liver injury, as shown by histopathology, decreased serum transaminases and improved oxidative status of the liver. Reduced collagen deposition and α-SMA immuopositive cells indicated an abrogation of hepatic stellate cell activation by OBE. Furthermore, OBE was highly effective in stimulating HGF mRNA and protein expression and inhibiting CCl4-induced CYP2E1 down-regulation. The mechanism of antifibrogenic action of OBE is hypothesized to proceed via scavenging free radicals and activating liver regeneration by induction of HGF. These data suggest the use of OBE as a complementary treatment in liver fibrosis.